Wood Decaying Fungi of Boswellia serrata Stored Wood - Tiwari, C. K.; Harsh, N. S. K.; , Jamaluddin (Indian Forester, 2005)
Boswellia serrata wood is economically important for various purposes, but is non-resistant to fungal decay. In all, 14 wood decay fungi were collected on B. serrata stored wood, 12 of them being recorded for the first time from Madhya Pradesh. One brown rot fungus was also recorded.